#TITLE_ALTERNATIVE# - TRI JOKO WIBOWO (NIM: 23407003), R.B.
Three major components for knowledge management are knowledge management enablers, knowledge management processes, and organizational performances. This research has focus at knowledge management enablers. Knowledge management implementation process is influenced by factors (critical success factors). Model Singh and Kant (2008) is one of theoretic models that show relationships among factors influencing knowledge management process. The aim of this research is not to design model but to confirm model Singh and Kant 2008). To achieve this aim, this research uses structural equation modeling (SEM) to analyze relationships among factors at that model. Data for SEM are collected from distributing questionaires to employees at PT Krakatau Steel. The major result from SEM analysis is that model has enough fit to real system. Goodness of fit indicators of model are p value : 0.00 = 0.05 (poor fit), GFI 0.72 = 0.90 (poor fit), RMSEA 0.060 = 0.08 (fit) CFI 0.95 = 0.90 (fit), NNFI 0.94 = 0.90 (fit) , NFI 0.88 = 0.90 (poor fit) dan AGFI 0.68 = 0.90 (poor fit). Addition, hypothetic tests for 10 hypothetic relationship among factors are that 9 hypothetic relationships are significant and that 1 hypothetic relationship is not significant. The conclussion is that this research's model is enough fit to real system. So, factors at this research’s model can be used to manage and control the knowledge management implementation process. The factors at this research's model are top management commitment, technological infrastucture, methodology, organizational structure, orgnizational culture, motivation and reward, staff retirement, staff defection and ownership of problem.